Microstructural and mechanical characterization of pre-used SA 335 P91 super-heater pipe weldment used in 70 MW CFBC boilers. (December 2022) - Prabu, S. Senthur; Sujai, S.; Prathiba, S.; Ramkumar, K. Devendranath; Arivazhagan, N.
The enhanced SA 335 P91 steels are specially designed to be used in the super-heaters in thermal power plants which are commonly operated at an elevated temperature. The present study involves an analysis of microstructure and the tensile property of the used P91 tubular steel of such heat exchanger in as-received conditions. The joints were fabricated by gas tungsten arc welding (GTAW) and shielded metal arc welding (SMAW) by employing ErNiCrMo-3 and E9018 B9 fillers. The microstructure showed the presence of flakes of martensite, formation of Nb-rich phases with an unmixed zone in the interface of the weld followed by the columnar and equiaxed dendrites in the centre of the weld zone, while employing the ERNiCrMo-3 filler in GTAW. Whereas in SMA welding, no such unmixed zone was observed while employing E9018 B9 filler except the precipitation of carbides. The metallurgical and mechanical characterization of welded joints was performed by optical microscope, scanning electron microscopy with energy dispersive spectroscopy (EDS), hardness, toughness and tensile tests. From the SEM/EDS analysis in the fusion zone of joints inferred the uniform distribution of the element with Nb phases and oxide formation in the pre used P91 steel for both the weldments irrespective of the fillers employed. Alongside the hardness of the SMA weld zone showed a higher hardness by the precipitation of M23 C6 and martensitic structure compared to the GTAW weld zone which is found to be lower owing to the presence of elements such as Mo, Nb, Al and C. In both the joints, the tensile failure occurred away from the fusion zone in the parent metal and SMAW joints imparted better strength than GTAW joints. The GTAW joints showed better toughness by ensuring the ductile mode of failure in fractography studies.